2000
DOI: 10.1161/01.cir.101.21.2467
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Miss

Abstract: These data support the hypothesis that the combination of injury and low-dose beta-radiation induces deleterious outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(33 citation statements)
references
References 21 publications
1
31
0
1
Order By: Relevance
“…The volumetric analysis on intracoronary ultrasound showed that the growth of neointimal tissue was mild after 6 months of clinical follow-up, a result similar to that of other studies 32 . The growth of the vessel (+21.4±27.8 mm 3 ) observed after 180 days of treatment suggests that intracoronary beta radiation induced a positive remodeling of the arterial wall, characterized by an "accommodative" process of the plaque (correlation of the increase in the ∆ external elastic membrane vs D plaque, r=0.963, P < 0.01), preserving the volume of the in-stent lumen.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The volumetric analysis on intracoronary ultrasound showed that the growth of neointimal tissue was mild after 6 months of clinical follow-up, a result similar to that of other studies 32 . The growth of the vessel (+21.4±27.8 mm 3 ) observed after 180 days of treatment suggests that intracoronary beta radiation induced a positive remodeling of the arterial wall, characterized by an "accommodative" process of the plaque (correlation of the increase in the ∆ external elastic membrane vs D plaque, r=0.963, P < 0.01), preserving the volume of the in-stent lumen.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with gamma radiation, beta radiation has a smaller depth of penetration, minimizing the exposure to radiation for patients and operators, requiring, therefore, less radioprotection. However, the rapid decrease in the dose of beta radiation within 2-5mm of depth is associated with a less homogeneous release of the dose 32 . In addition, the "shield effect" produced by the rods of the stent could be associated with an attenuation in the radiation dose through its rods greater than 15% 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The IRS was defined as the area encompassed by the 2 gold markers of the radiation source train. 5 It was identified on angiography by contrast injection with the source in place.…”
Section: Angiographic Analysismentioning
confidence: 99%
“…10 -12 It is anticipated this rate will be reduced by optimization of antiplatelet regimens (and hence a reduction in stent thrombosis), adjustments to the dose prescription, and more meticulous attention to irradiating the entire ballooninjured segment (to reduce the occurrence of "geographic miss"). 16 However, among the 150 000 patients who undergo treatment for in-stent restenosis annually in the United States, there remains a population of patients who will encounter recurrent restenosis despite optimal intracoronary brachytherapy.…”
Section: Discussionmentioning
confidence: 99%